2007
DOI: 10.1098/rsbl.2006.0617
|View full text |Cite
|
Sign up to set email alerts
|

A fossil brain from the Cretaceous of European Russia and avian sensory evolution

Abstract: Fossils preserving traces of soft anatomy are rare in the fossil record; even rarer is evidence bearing on the size and shape of sense organs that provide us with insights into mode of life. Here, we describe unique fossil preservation of an avian brain from the Volgograd region of European Russia. The brain of this Melovatka bird is similar in shape and morphology to those of known fossil ornithurines (the lineage that includes living birds), such as the marine diving birds Hesperornis and Enaliornis, but doc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
31
2
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 14 publications
4
31
2
1
Order By: Relevance
“…There also is no apparent folding of the cerebellum as in avialans (Kurochkin et al, 2005) and oviraptorosaurs (Kundrá t, 2007;Balanoff et al, 2007). Lateral to the cerebellum are the paired floccular lobes (fig.…”
Section: Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…There also is no apparent folding of the cerebellum as in avialans (Kurochkin et al, 2005) and oviraptorosaurs (Kundrá t, 2007;Balanoff et al, 2007). Lateral to the cerebellum are the paired floccular lobes (fig.…”
Section: Descriptionmentioning
confidence: 99%
“…The cerebellum is compressed mediolaterally and lacks the lateral expansion present in avialans (Dominguez-Alonso et al, 2004;Kurochkin et al, 2005). There also is no apparent folding of the cerebellum as in avialans (Kurochkin et al, 2005) and oviraptorosaurs (Kundrá t, 2007;Balanoff et al, 2007).…”
Section: Descriptionmentioning
confidence: 99%
“…Although it does not account for evolutionary relationships (see Felsenstein, 1985), the encephalization index is still the most widely used metric to discern whether the volume of an endocast is more typical of ''avians'' or ''paraphyletic reptiles'' (i.e., Reptilia in the noncladistic sense, lacking Aves) (Jerison, 1969;Hopson, 1977Hopson, , 1979Alonso et al, 2004;Kurochkin et al, 2007). The encephalization index of the oviraptorid Conchoraptor gracilis falls within the range of avians (Kundrá t, 2007); thus, ostensibly showing another avian similarity.…”
Section: Endocranial Morphology Figures 15-17mentioning
confidence: 99%
“…enlarged cerebellum and reduced olfactory bulbs) relative to the brain of non-avian theropods to meet flight requirements. Indeed, many studies have suggested that the brain architecture of extant birds may not have evolved until the advent of more derived, and presumably more agile, ornithurine birds (Larsson et al 2000;Kurochkin et al 2007). …”
Section: Phylogenetic Implicationsmentioning
confidence: 99%